(untitled) (Research, Society and Development, 2025)
Inhalational anesthesia is central to routine small animal surgery, allowing precise control of anesthetic depth and predictable recovery. Among the most commonly used volatile agents are isoflurane, sevoflurane, and desflurane, whose pharmacological, clinical, economic, and environmental profiles guide their selection. The objective of this study is to analyze the use of these anesthetics in veterinary practice, describing pharmacological characteristics, comparing clinical efficiency (induction, maintenance, and recovery), evaluating safety (well-being and perioperative risks), and discussing challenges/advances, identifying gaps for research. A narrative review was conducted in the PubMed, SciELO, and Google Scholar databases, including studies in Portuguese and English that address efficacy, safety, cost, and environmental aspects in dogs and cats; standardized extraction and descriptive-comparative analysis of the findings. In the results, sevoflurane generally presents faster induction and recovery and a good cardiorespiratory profile, favoring pediatric, geriatric, or clinically unstable patients; isoflurane maintains widespread use due to its lower cost, although with slower induction/recovery and a greater propensity for hypotension in prolonged or critical scenarios; desflurane offers very rapid awakening, but can irritate the airways and requires greater investment (agent and vaporizer), restricting its diffusion. In terms of sustainability, all contribute to emissions; desflurane has a greater climate impact, and iso/sevo has a smaller, but still relevant, impact. It is concluded that there is no universally superior agent; the choice should be contextual and guided by safety, cost-effectiveness, and environmental mitigation. Institutional protocols, rigorous monitoring, and multicenter studies are recommended to qualify anesthetic decisions in small animals.